2017
DOI: 10.18632/oncotarget.17563
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide and angiotensin II have inhibitory effects on HERG protein expression: Evidence for the role of PML SUMOylation

Abstract: The human ether-a-go-go-related gene (HERG) channel is a novel target for the treatment of drug-induced long QT syndrome, which causes lethal cardiotoxicity. This study is designed to explore the possible role of PML SUMOylation and its associated nuclear bodies (NBs) in the regulation of HERG protein expression. Both arsenic trioxide (ATO) and angiotensin II (Ang II) were able to significantly reduce HERG protein expression, while also increasing PML SUMOylation and accelerating the formation of PML-NBs. Pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…This study revealed that long-term ATO suppressed the I Kr current in HEK293 cells, and the dosage of ATO directly determined the reduction degree of I Kr ( Ficker et al, 2004 ). The same phenomenon can also be observed in other HEK293 experiments ( Zhao et al, 2015 ; Yan et al, 2017 ), and the inhibiting effect of ATO on the hERG channel has also appeared in rodent animals, such as guinea pig VMs ( Ficker et al, 2004 ; Zhao et al, 2014 ), neonatal rat VMs (NRVMs) ( Zhao et al, 2015 ), and neonatal mouse cardiomyocytes ( Liu et al, 2017 ). In addition, the underlying RNA regulation mechanisms of ATO-impaired hERG were revealed ( Shan et al, 2013 ; Zhao et al, 2015 ).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This study revealed that long-term ATO suppressed the I Kr current in HEK293 cells, and the dosage of ATO directly determined the reduction degree of I Kr ( Ficker et al, 2004 ). The same phenomenon can also be observed in other HEK293 experiments ( Zhao et al, 2015 ; Yan et al, 2017 ), and the inhibiting effect of ATO on the hERG channel has also appeared in rodent animals, such as guinea pig VMs ( Ficker et al, 2004 ; Zhao et al, 2014 ), neonatal rat VMs (NRVMs) ( Zhao et al, 2015 ), and neonatal mouse cardiomyocytes ( Liu et al, 2017 ). In addition, the underlying RNA regulation mechanisms of ATO-impaired hERG were revealed ( Shan et al, 2013 ; Zhao et al, 2015 ).…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, lead compound optimization was also reported to be a strategy that alleviated ATO toxicity ( Zhou et al, 2016 ). In addition, the regulatory mechanism of TGF-β1 under ATO treatment ( Chu et al, 2012 ; Liu et al, 2017 ) provided new methods for preventing hERG and Kir2.1 protein damage by treatment with the protein kinase A (PKA) antagonist H89 and the TβR-I inhibitor LY364947 ( Chu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, such as arsenic trioxide (ATO), angiotensin‐II (Ang II), and FBS, are reported to trigger the PML SUMOylation (Y. Liu, Li et al, ; Xu, Liu, Wu, Qiao, & Yan, ). In the current study, we found that TGF‐β1 dramatically triggered PML SUMOylation (Figure a,b) in a dose‐ and time‐dependent manner, which was well consistent with TGF‐β1‐mediated and increased its own expression (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…In the formation and degradation of PML‐NB, several factors play key roles in localization of proteins, for instance, SUMOylation, a process of posttranslational modification of proteins by the SUMO family of proteins, is known to be involved in yeast and mammalian somatic cell‐cycle regulation, including signal transduction, protein trafficking, chromosome segregation, and DNA repair (Feitosa & Morris, ). The PML SUMOylation can be enhanced by a variety of stimuli, including interferon (IFN), FBS, CdCl 2 , Ang II, heat shock, DNA damage, and ATO (Y. Liu, Li et al, ; Y. Liu, Zhao, ; Sahin et al, ); and the PML‐NBs can be formed immediately after PML is recruited into the nucleus. Here, we found that PML SUMOylation can be enhanced by TGF‐β1 as a new stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed rectifying potassium current ( I kr ) channel protein on human cardiomyocytes is encoded by human hERG. Studies demonstrated that the loss of hERG function and the inhibition of I kr caused by drugs prolonged QT interval and possibly induced TdP, thus leading to fatal arrhythmias ( Liu et al, 2017 ). Some toxic CMM induce cardiotoxicity by directly inhibiting the expression of hERG channel protein or coding gene to suppress potassium channels.…”
Section: Mechanisms Of Cmm-induced Cardiotoxicitymentioning
confidence: 99%